THE ROLE OF SEX HORMONES (FSH, LH) IN THE DEVELOPMENT OF CARIOUS AND NON-CARIOUS DENTAL DISEASES IN HYPERPARATHYROISIS (International Bulletin of Medical Sciences and Clinical Research, 2023)
In the development of structural changes in teeth, the level of calcium in the blood is of great importance, which is controlled by parathyroid hormone and thyroid calcitonin, dysfunction and imbalance of which can cause irreversible, severe consequences for the body.